Orbital atherectomy for treating calcified iliac artery disease to enable large bore device delivery: A case series report. (July 2020) - Rao, Siddhartha; Martinsen, Brad J; Higgins, Joseph; Dhandhusaria, Henisha; Patel, Dwijesh
The current standard of care for the treatment of flow-limiting calcific iliac artery disease is balloon angioplasty and subsequent stent placement. However, the presence of calcified lesions may prevent adequate stent expansion or impede the delivery of large bore devices, such as those for transcatheter aortic valve replacement or endovascular aneurysm repair implants. Plaque modification through vessel preparation with orbital atherectomy may enable stent expansion and subsequent proper large device delivery with low rates of procedural complications. A retrospective, single center, case series of 13 subjects treated with orbital atherectomy in iliac arteries to enable large bore device delivery was conducted. Patients were selected for treatment based on iliac artery disease or inability to deliver devices. The procedural complication rate was defined as the composite of flow-limiting dissection, perforation, slow flow, vessel closure, spasm, embolism, and thrombosis. Technical success was assessed as angiographic luminal gain and subsequent successful delivery of large bore devices through the treatment area, as well as freedom from procedural complications. Orbital atherectomy vessel preparation of severely calcified iliac artery lesions resulted in adequate stent expansion safely and enabled delivery of rigid/large profile devices. Further studies are warranted to evaluate patient selection criteria, as well as long-term efficacy and safety rates of orbital atherectomy in the iliac artery.